2019
DOI: 10.1177/0306624x19849569
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study on Self-Reported Psychopathy and Criminal Recidivism Among Incarcerated Male Juvenile Offenders

Abstract: The present study examines the utility of three self-report measures of psychopathic traits in predicting recidivism among a sample of incarcerated male juvenile offenders. Participants ( N = 214, M = 16.40 years, SD = 1.29 years) from seven Portuguese juvenile detention centers were followed and prospectively classified as recidivists versus non-recidivists. Area under the curve (AUC) analysis revealed that the Antisocial Process Screening Device–Self-Report (APSD-SR) presented the best performance in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 60 publications
1
7
0
3
Order By: Relevance
“…The only exception to this was the interaction between crime frequency and callous-unemotional traits in predicting general recidivism. Although not supportive of our hypotheses, the limited associations between psychopathic features and recidivism among youth measured using a self-report format (e.g., APSD-SR, Youth Psychopathic Traits Inventory--YPI, YPI-Triarchic-Short) was consistent with most prior research (e.g., Colins et al, 2012b;Colins et al, 2017;Pechorro et al, 2019;Pechorro et al, 2021), but discordant with other research (e.g., Goulter et al, 2018;Salekin, 2008). On the other hand, research has demonstrated that psychopathy as conceptualized by the PCL: YV using a rating scale format is predictive of recidivism (Gretton et al, 2004;McCuish et al, 2015), even after removing its antisocial factor (e.g., Vitacco et al, 2005;Walters et al, 2008), but effects that are significant are seen among boys not girls (Colins et al, 2017;Vincent et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…The only exception to this was the interaction between crime frequency and callous-unemotional traits in predicting general recidivism. Although not supportive of our hypotheses, the limited associations between psychopathic features and recidivism among youth measured using a self-report format (e.g., APSD-SR, Youth Psychopathic Traits Inventory--YPI, YPI-Triarchic-Short) was consistent with most prior research (e.g., Colins et al, 2012b;Colins et al, 2017;Pechorro et al, 2019;Pechorro et al, 2021), but discordant with other research (e.g., Goulter et al, 2018;Salekin, 2008). On the other hand, research has demonstrated that psychopathy as conceptualized by the PCL: YV using a rating scale format is predictive of recidivism (Gretton et al, 2004;McCuish et al, 2015), even after removing its antisocial factor (e.g., Vitacco et al, 2005;Walters et al, 2008), but effects that are significant are seen among boys not girls (Colins et al, 2017;Vincent et al, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…358 Martin, 2013). Though the characteristics of psychopathy and antisocial personality disorders were related to recidivism, there was not one instrument or finding which predicts poor outcomes (Pechorro, Seto, Ray, Alberto, & Simões, 2019). Students in juvenile detention need more intensive services than a second-tier intervention or 20 minutes extra per day for response to intervention.…”
Section: Resultsmentioning
confidence: 99%
“…It is recognised that psychopathology and particularly the diagnosis of either personality disorder or substance use disorder are associated with an increased risk of recidivism in criminals (Ducat et al., 2017; Walter et al., 2011). Especially the psychopathic traits (impulsivity, affective shallowness and interpersonal maladjustment) increase the risk of violent behaviour and recidivism (Leung et al., 2019; Pechorro et al., 2019; Stone, 2002). On the other hand, although Cluster B personality disorders have been associated with recidivism (Tikkanen et al., 2009) due to their common characteristics, such as impulsivity and emotional dysregulation, it is true that narcissistic personality traits by definition are somewhat different from this type of dysfunctionality and are characterised by a more measured and adapted lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that having a criminal history has been identified as one of the strongest predictors of reoffending (Andrews & Bonta, 2010; Leung et al., 2019; Maden et al., 2006), participants were classified based on: (1) recidivists: inmates who had already served time period of sentence for one or several other crimes in prison and (2) non‐recidivists: prisoners serving their first sentence in prison. This classification was made taking to account previous studies where prior criminal history was used to assess recidivism (Fazel, Chang et al., 2016; Fazel, Hayes et al., 2016; Leung et al., 2019; Pechorro et al., 2019). In this study, to objectify the variable, a measure of institutionalised recidivism was used, and in other words, how many times the participant has had a conviction and prison sentence for committing a crime.…”
Section: Methodsmentioning
confidence: 99%